(untitled) (Journal of International Studies, 2025)
This study explores the relationship between motivational factors (including hygiene factors) and intelligence factors (cultural intelligence and social intelligence) on expatriates’ intention to stay and continue working in Pakistan. Additionally, it investigates the mediating role of job satisfaction and the moderating role of social infrastructure in these relationships. A quantitative research approach was adopted, with data gathered through survey questionnaires from a sample of 303 expatriates working in three major Pakistani cities, namely Lahore, Islamabad, and Karachi were involved in this study. The findings reveal a significant and positive relationship between motivational factors, hygiene factors, cultural intelligence, and social intelligence with job satisfaction. Regarding expatriates’ intention to stay, all independent variables showed a significant relationship, except for cultural intelligence. Furthermore, job satisfaction was found to be positively associated with expatriates’ intention to stay and mediated the relationship between motivational factors, hygiene factors, cultural intelligence, and social intelligence with expatriates’ retention intentions. However, the results indicate that social infrastructure does not moderate the relationship between job satisfaction and expatriates’ intention to stay. This study contributes to the existing literature on expatriate retention and offers useful insights for firms and policymakers on the key factors that influence expatriates’ decision to remain in a country.